2021
DOI: 10.1186/s12871-021-01536-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of erector spinae plane block on perioperative opioid consumption and rehabilitation in video assisted thoracic surgery

Abstract: Background This study aimed to determine whether ultrasound-guided continuous erector spinae plane block (ESPB) had an effect on opioid consumption and postoperative rehabilitation in patients undergoing video-assisted thoracic surgery (VATS). Methods In this prospective study, 120 patients aged 20–70 years who underwent elective VATS were randomly allocated to one of three groups: group C (general anesthesia with patient-controlled intravenous ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…An effective analgesic administration accelerates recovery, contributes to the early mobilization of patients, and reduces hospital stay [ 2 , 3 ]. Thoracic epidural analgesia (TEA) is the most commonly used and still accepted gold standard method in the treatment of post-thoracotomy pain [ 4 ]. However, serious complications such as dural puncture, sympathetic block, spinal hematoma, and epidural abscess can also be seen due to epidural application [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An effective analgesic administration accelerates recovery, contributes to the early mobilization of patients, and reduces hospital stay [ 2 , 3 ]. Thoracic epidural analgesia (TEA) is the most commonly used and still accepted gold standard method in the treatment of post-thoracotomy pain [ 4 ]. However, serious complications such as dural puncture, sympathetic block, spinal hematoma, and epidural abscess can also be seen due to epidural application [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, serious complications such as dural puncture, sympathetic block, spinal hematoma, and epidural abscess can also be seen due to epidural application [ 5 ]. Thoracic paravertebral block (TPVB) application has also been used in recent years due to the lower incidence of side effects such as hypotension, urinary retention, and nausea and vomiting compared to TEA [ 4 , 6 ]. With the widespread use of ultrasound (US) in recent years, different thoracic wall block techniques, which are claimed to cause fewer complications, have begun to be applied [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with the previous study that postoperative pain at rest and coughing in continuous ESP block were significantly higher than TEA 24 hours after surgery. 28 On the contrary, Nagaraja et al 10 have reported comparable pain scores in both TEA and ESP block groups in the early postoperative period after cardiac surgery and that an ESP block might be superior to TEA at 24 h, 36 h, and 48 h, both at rest and while coughing.…”
Section: Discussionmentioning
confidence: 97%
“…When the placement of a thoracic epidural is not possible, ESP catheters can be utilized to manage postoperative pain after thoracotomy [6,11]. These can be done either unilaterally or bilaterally, depending on the surgery performed.…”
Section: Discussionmentioning
confidence: 99%
“…One case series of 42 patients demonstrated that when performed at the T5 level, the patients had decreased sensation in a dermatomal distribution from T3 to T10, with no significant adverse effects [6]. While several studies demonstrate ESP blocks' efficacy in minimizing opioids for various thoracic surgeries [6,11], there is very little in the literature about using ESP catheters in lung transplant patients.…”
Section: Discussionmentioning
confidence: 99%